2022
DOI: 10.1002/ctm2.801
|View full text |Cite
|
Sign up to set email alerts
|

Key role of quorum‐sensing mutations in the development of Staphylococcus aureus clinical device‐associated infection

Abstract: Dear Editor, In the present study, we show that the development of Staphylococcus aureus device-associated infection involves mutations in the quorum-sensing system Agr that increase biofilm formation and thereby bacterial resistance to antibiotics.The enormous difficulty clinicians face in the treatment of device-associated infections is due to the characteristic involvement of biofilms, which are bacterial agglomerations that form on the device surface and exhibit considerably increased resistance to virtual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Contrastingly, Agr has the opposite effect on infections that are chronic and involve biofilms, such as infections of indwelling medical devices, prosthetic joint infections, or cystic fibrosis [ 19 , 41 , 42 , 43 ]. It also, somewhat paradoxically, promotes persistence in osteomyelitis [ 44 ].…”
Section: Impact Of Agr Control On S Aureus Infecti...mentioning
confidence: 99%
See 2 more Smart Citations
“…Contrastingly, Agr has the opposite effect on infections that are chronic and involve biofilms, such as infections of indwelling medical devices, prosthetic joint infections, or cystic fibrosis [ 19 , 41 , 42 , 43 ]. It also, somewhat paradoxically, promotes persistence in osteomyelitis [ 44 ].…”
Section: Impact Of Agr Control On S Aureus Infecti...mentioning
confidence: 99%
“…This is often due to its exceptionally strict control of PSMs, which structure biofilms and lead to biofilm dispersal [ 45 ], and facilitate escape from host cells [ 46 ]. In the absence of PSMs in Agr dysfunctional mutants, biofilms grow thicker and more compact, which leads to increased resistance to leukocyte attacks and antibiotics [ 42 , 43 ]. In many host cells, the absence of Agr-controlled factors, including PSMs, leads to intercellular persistence [ 47 , 48 ].…”
Section: Impact Of Agr Control On S Aureus Infecti...mentioning
confidence: 99%
See 1 more Smart Citation
“…18 Dysfunctional mutations of the agr system help to suppress S. aureus skin and intestinal colonization, 19,20 which are nonimplant-associated infections. However, we recently found that S. aureus agr-dysfunctional mutants could be isolated from clinical cases of surgical implant-associated infection 21 and that prolonged infection increased the rate of agr-dysfunctional mutant development. Our previous in vivo observations revealed that agr-dysfunctional isolates could form robust and enlarged biofilms on the implant surface to increase the resistance of agr-dysfunctional biofilms to leukocyte attacks.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, while these data provide an explanation for mixed populations in toxigenic infections, they do not account for chronic, biofilm-associated clinical S. aureus infections where homogeneous agr -negative populations can rapidly emerge [112]. It should also be noted that S.…”
Section: Introductionmentioning
confidence: 99%